The prediction of depression based on religious coping and the components of positive youth development in adolescents - Sarizadeh, Mohammad Sadegh (Mental health, religion & culture, 2020)
This study aimed to predict depression based on religious coping and components of positive youth development in adolescents. The statistical population of the study covers all high-school students in Semnan, Iran. Using multi-stage cluster sampling, 383 subjects completed the Children's Depression Inventory, Positive Youth Development-Very Short Form Scale, and Brief Religious Coping Scale. The results demonstrated that negative religious coping was positively and significantly associated with depression. Positive Youth Development components and positive religious coping were negatively and significantly related to depression. The results of regression revealed that components of confidence, negative religious coping, positive religious coping, caring, connection, character, and gender are the predictors of depression and they are defining 52% of the total variance of depression. Findings are suggesting that attention should be paid to Positive Youth Development programmes and religious coping of adolescents to prevent and reduce depression.